Post‐fire recovery of litter detritivores is limited by distance from burn edge. (29th June 2016) - Arnold, Kate T.; Murphy, Nicholas P.; Gibb, Heloise
Abstract: Climate change is likely to result in an increased frequency of extreme fire events, including more large‐extent wildfires. The effects of fire extent on post‐fire faunal recovery are poorly understood. Effects on invertebrate detritivores are of particular interest due to their functional importance in litter breakdown. We asked if distance from fire edge affected the composition and morphological traits of a key group of large invertebrate detritivores: cockroaches (Blattodea) 6 years after fire. We used six replicate transects in herb‐rich foothill habitat in areas that were severely burnt during the 2009 Black Saturday fires, north‐east of Melbourne, Australia. Transects extended from unburnt controls up to 5 km into large extent burns. Habitat variables were measured and cockroach abundances were recorded using artificial habitats comprised of stacked egg trays. Cockroach morphological traits were recorded in the laboratory. Multivariate generalized linear models revealed that habitats varied with transect, but not distance into the burn, suggesting recovery of habitat features relevant to cockroaches. Distance from burn did not affect the species richness or abundance of cockroaches, but both richness and abundance increased with bark and litter cover and decreased at lower temperatures. Cockroach assemblage composition responded significantly to distance into burn, transect and habitat variables, although only Platyzosteria similis was negatively associated with distance into the burn. Fourth corner models including traits did not provide greater predictive power than models including only species abundances and environmental variables. Wing presence, which was associated with smaller body size, did not affect site occupancy. Although species traits did not predict cockroach responses, our work shows that distance into a fire, a surrogate for fire extent, continued to be an important determinant of post‐fire assemblages 6 years after fire. An increase in large‐extent fires may reduce the recolonization potential of some cockroach species, potentially limiting their functional importance in litter breakdown.